THE SIGNIFICANCE OF THE PEARLS INTERNATIONAL ASSESSMENT PROGRAM IN IMPROVING THE QUALITY OF EDUCATION - Hasanova Sabohat Komil qizi (Scholars Digest Publishing, 2024)
While reading this article, the importance and possibilities of PIRLS international assessment program in improving the quality of education were considered. The method of organizing tasks based on unusual topics in improving the reading skills of primary classes was also considered.
Keywords: PIRLS international assessment program, methodology, quality of education, primary school students and teachers, unusual topics.